Caracterización de los áridos del río dos mangas y cantera del cerro el tablazo de la provincia de Santa Elena para utilizarlo como material de construcción - Sánchez Luna, Tania (2011)
The work that is presented in this project contains information about the arids extracted from the quarry of the hill El Tablazo, located in Santa Elena City, and the Dos Mangas river, located in Manglaralto , the same that are used in several works of civil engineering in all the province of Santa Elena, such as bases, sub bases of roads, landfills, improvement of soils for foundations, breakwaters and manufacture of concretes and mortars. Also there is a study of the classifications of these materials, procedure that must be accomplished and applications in the field of construction. The materials extracted from the locations previously mentioned were submitted to laboratory test programs in order to determinate their properties and physic and mechanical characteristics and then establish if they are suitable for use it in the construction of sub bases of roads and landfills evaluating them according the specifications MOP - 001F - 2002.